Electrocardiography in height - Sáenz Jiménez, Ricardo (1939)
The work of Professor Monge et al on pulse, blood pressure and cardio-vascular response to exercise needed to be completed with the help of elkectrocardiográfico method, if any advantage is on the methods used in previous research, it is to be a graphical method and mathematical precision.